Features of Digital Markets Functioning - M. G. Goloventchik; G. G. Goloventchik (Цифровая трансформация, 2023)
The transition from an industrial society to an open information society based on digital technologies is accompanied by the formation and becoming of a digital market, which objectively requires increased attention of scientists to a comprehensive and more detailed study of socio-economic problems and the development of the consequences of this process. Due to the relevance of the proposed topic, the article examines the essence of objects and subjects of a digital market, highlights the speciﬁcs of digital goods and services. It reveals the content of e-commerce as the main segment of a digital market, gives a brief description of a digital services market.